Constructing belonging through mediated memory: multimodal perception and narrative semantics in war films - Zheng, Jiaqi; Huang, Tianle; Wang, Song; Wang, Zhaoqiang (Frontiers in Psychology, 2025)
This study investigates how contemporary Chinese war films construct a sense of belonging among domestic audiences through three interrelated perceptual modalities: emotional expression, semantic cues, and musical structure. Grounded in the framework of media memory theory, the research analyzes a corpus of high-grossing films using facial expression recognition (FaceReader), semantic clustering (BERT embeddings), and soundtrack analysis (MuseNet-based modeling). Audience feedback was collected via online questionnaires (N = 379, aged 18–60) to validate the affective resonance of selected “core clips.” Statistical comparisons were performed to identify the relative influence of each modality. Results suggest that patterns of national identity, moral resonance, and emotional synchrony converge to shape a distinctive aesthetic of belonging. This study contributes to a deeper understanding of how media memory transforms affective experiences into collective identification, while also reflecting on the methodological boundaries between subjective interpretation and computational objectivity.